Model Evaluasi Program Pendidikan Terhadap Peningkatan Kualitas Pembelajaran - Iqbal, Muhammad; Savitri, Intan; Hanifah, Fathia; Alfiana Kholizah, Nur; Sari, Dinda Aulia; Munawwarah, Tarisa (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The quality of education in an educational institution is currently one of the important elements in the sustainability of the educational institution itself, both in terms of the quality of infrastructure, the quality of teaching and education staff or the quality of learning, all of this is one unit that must be maintained and updated in order to make education quality. An educational evaluation model, where matters related to evaluation data are collected is the main step in conducting educational evaluations, especially the quality of learning. Through research using this qualitative method, the author intends to provide readers with views regarding educational evaluation models, especially evaluations that lead to improving the quality of learning with appropriate steps. Evaluation models may appear to vary from one another, but the aims and objectives are the same, namely carrying out data or information collection activities relating to the object being evaluated.